Polymer fullerene solution phase behaviour and film formation pathways - Dattani,R; Cabral,JT (Soft Matter, 2015)
We report the phase behaviour of polymer/fullerene/solvent ternary mixtures and its consequence for themorphology of the resulting composite thin films. We focus particularly on solutions of polystyrene (PS), C60fullerene and toluene, which are examined by static and dynamic light scattering, and films obtained fromvarious solution ages and thermal annealing conditions, using atomic force and light microscopy.Unexpectedly, the solution phase behaviour below the polymer overlap concentration, c, is found to bedescribed by a simple excluded volume argument (occupied by the polymer chains) and the neatC60/solvent miscibility. Scaling consistent with full exclusion is found when the miscibility of the fullerenein the solvent is much lower than that of the polymer, giving way to partial exclusion with more solublefullerenes (phenyl-C61-butyric acid methyl ester, PCBM) and a less asymmetric solvent (chlorobenzene),employed in photovoltaic devices. Spun cast and drop cast films were prepared from PS/C60/toluenesolutions across the phase diagram to yield an identical PS/C60 composition and film thickness, resultingin qualitatively different morphologies in agreement with our measured solution phase boundaries. Ourfindings are relevant to the solution processing of polymer/fullerene composites (including organicphotovoltaic devices), which generally require effective solubilisation of fullerene derivatives and polymerpairs in this concentration range, and the design of well-defined thin film morphologies.